The Dilemma of Hospitality: Revisiting Indonesia's Policy on Handling Refugees Under International Law - Ganesh Cintika Putri (Badan Strategi Kebijakan Hukum, 2022)
Presidential Regulation No. 125 of 2016 is the first regulation that provides a normative framework to manage refugees and asylum seekers in Indonesia. However, many scholars believe that this regulation is simply an institutionalization of several existing informal practices, and it does not introduce any substantive changes to ensure refugee protection. This paper analyzes the content of the Presidential Regulation, including its background, structure, wording, and its aims. In addition, this study identifies the limits of the regulation in fulfilling, protecting, and respecting human rights based on the international human rights instruments. This article contends that the Presidential Regulation portrays what I call dilemma of hospitality. It reflects on the one hand, the regulation welcomes the refugees by providing mandates to the authorities to rescue those stranded at sea and to provide accommodation during their stay. On the other hand, the regulation implies a kind of distrust to the refugees